2016
DOI: 10.1186/s12955-016-0494-7
|View full text |Cite
|
Sign up to set email alerts
|

Czech version of OPQOL-35 questionnaire: the evaluation of the psychometric properties

Abstract: BackgroundBoth prognoses and real demographic trends in developed countries point to the increasing proportion in the population of people above 65 years of age. One of important themes of care for seniors is the assessment of their quality of life. To evaluate the quality of life of seniors three types of tools can be used: general generic tools; generic tools used for the age group of elderly persons; specific tools to detect the quality of life of the elderly who are affected by specific diseases.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…It has been shown that QoL is a strong predictor of adverse health outcome, such as death in older people, and its evaluation is an important point for policymakers [3,7,13]. QoL in old age covers a variety of dimensions including: health condition and functional ability, sense of being useful for other people, social relationships, social support, financial situation, and the quality of housing [14,15]. To properly evaluate older people's quality of life, it is necessary to consider all various physical, mental, and social aspects of QoL using an appropriate scale [1,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that QoL is a strong predictor of adverse health outcome, such as death in older people, and its evaluation is an important point for policymakers [3,7,13]. QoL in old age covers a variety of dimensions including: health condition and functional ability, sense of being useful for other people, social relationships, social support, financial situation, and the quality of housing [14,15]. To properly evaluate older people's quality of life, it is necessary to consider all various physical, mental, and social aspects of QoL using an appropriate scale [1,16].…”
Section: Introductionmentioning
confidence: 99%
“…It was the same for the term "things I would enjoy" in statement 29 ("I cannot afford to do things I would enjoy"). Mares et al (2016) amended this term to "things I would like to have" in the Czech version, and these statement was not included at all in the Iranian version (Nikkhah et al, 2018). To make these two terms…”
Section: Discussionmentioning
confidence: 99%
“…In the Czech version, Mares et al (2016) reversed the five-grade scale and adopted the Czech school grading system, which is more familiar to older people living there. Similarly, the Chinese version interpreted "leisure and social activities" as two separate dimensions, while the original English version includes them in the same dimension (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Del mismo modo, en el año 2008 Ann Bowling e investigadores de la universidad de Gran Bretaña desarrollaron el cuestionario denominado: "Calidad de Vida de las Personas Mayores" (OPQOL-35) en su idioma original, en el cual se empleó una muestra de 987 adultos mayores ingleses de más de 65 años, para sustentar su hipótesis que describe a la calidad de vida como un constructo multifactorial (Bowling & Rai, 2009;Mares, Cigler & Vachkova, 2016), posteriormente se publica su versión corta OPQOL-Bref en el 2013 que consta de 13 ítems considerados los más importantes por los encuestados, descartando 22 ítems del cuestionario original, demostrando ser una herramienta útil cuando se requiere una evaluación corta e implacable (Bowling et al, 2013), de igual manera se han realizado investigaciones para validar las versiones traducidas del cuestionario; es el caso de una muestra de 478 participantes, quienes reflejaron niveles altos de satisfacción en su calidad de vida, en siete dominios principales, quienes mantienen autonomía en sus actividades diarias y viven solo o con pareja, a diferencia de aquellos que se encuentran bajo el cuidado de residencias, tutores, familiares; la validez y confiablidad en esta investigación osciló entre 0.72 y 0.90 para su versión en checo (Mares, Cigler & Vachkova, 2016), referente a su versión reducida que consta de 7 dimensiones, se realizó la validación en 168 participantes para su versión en turco, donde se encontró que el cuestionario es rentable y cuenta con una buena consistencia interna para el resultado de sus subescalas (Caliskan et al, 2019), 521 personas adultas mayores que viven solas participaron en un estudio que utilizó la versión adaptada al idioma chino, presentando resultados confiables en las 8 dimensiones y ubicándolo como instrumento idóneo para evaluar la calidad de vida en adultos mayores que viven solos (Chen & While, 2019), en otro contexto sociocultural participaron 764 adultos mayores quienes respondieron el cuestionario en su versión e idioma original, reflejando que la calidad de vida está estrechamente relacionado a una buena salud física y emocional, independencia, toma de decisiones y control sobre su vida (Siriwardhana et al, 2019), en su versión persa los resultados de 500 y 525 participantes demostraron su utilidad para evaluar la calidad de vida en edades avanzadas para población de habla persa (Nikkhah et al, 2018;Feizi & Heidari, 2020).…”
Section: Introductionunclassified